The New worlds of Thomas Robert Malthus rereading the principle of population - Bashford, Alison; Chaplin, Joyce E. (Princeton University Press, 2016)
This book is a sweeping global and intellectual history that radically recasts our understanding of Malthus's Essay on the Principle of Population, the most famous book on population ever written or ever likely to be. Malthus's Essay is also persistently misunderstood. First published anonymously in 1798, the Essay systematically argues that population growth tends to outpace its means of subsistence unless kept in check by factors such as disease, famine, or war, or else by lowering the birth rate through such means as sexual abstinence. Challenging the widely held notion that Malthus's Essay was a product of the British and European context in which it was written, Alison Bashford and Joyce Chaplin demonstrate that it was the new world, as well as the old, that fundamentally shaped Malthus's ideas.